2021
DOI: 10.15690/vsp.v20i3/2271
|View full text |Cite
|
Sign up to set email alerts
|

Scoping Review Methodology: History, Theory and Practice

Abstract: The number of literature reviews is growing every year. One relatively new type of review is the scoping review (ScR). Only a handful of such studies have been produced in Russian academia. It is, therefore, crucial to inform Russian-speaking audiences about the history and evolution of the ScR methodology, the stages and features of such a study, and relevant international guidelines. Relevant data is presented in this narrative review. A PRISMA-ScR checklist has also been translated, taking into account reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 55 publications
(156 reference statements)
0
1
0
1
Order By: Relevance
“…The review was reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews (PRISMA-ScR) [15,16] . The MEDLINE electronic database was searched between January 1994 and September 2022 using the following keywords: (“Bipolar disorder” OR “bipolar affective disorder” OR “bipolar depression” OR “mania” OR “hypomania”) AND (“eating disorders” OR “anorexia nervosa” OR “bulimia nervosa” OR “binge eating disorders”) AND (“prevalence” OR “frequency” OR “comorbidity” OR “clinical features”).…”
Section: Methodsmentioning
confidence: 99%
“…The review was reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews (PRISMA-ScR) [15,16] . The MEDLINE electronic database was searched between January 1994 and September 2022 using the following keywords: (“Bipolar disorder” OR “bipolar affective disorder” OR “bipolar depression” OR “mania” OR “hypomania”) AND (“eating disorders” OR “anorexia nervosa” OR “bulimia nervosa” OR “binge eating disorders”) AND (“prevalence” OR “frequency” OR “comorbidity” OR “clinical features”).…”
Section: Methodsmentioning
confidence: 99%
“…Систематическое обзорное исследование литературы проведено в соответствии с руководством института имени Джоанны Бриггс [11] и оформлено в соответствии с рекомендациями надлежащей публикационной практики PRISMA-ScR [12,13].…”
Section: материал и методыunclassified